Gp91phox NADPH oxidase modulates litter size by regulating mucin1 in the uterus of mice. (4th March 2017) - Hiramoto, Keiichi; Yamate, Yurika; Sato, Eisuke F.
ABSTRACT: Active oxygen derived from gp91phox is critical for gestation. However, no reports have evaluated the relationship between reactive oxygen species (ROS) and the number of births in a given pregnancy. In this study, we examined the influence of ROS produced by gp91phox activity on the number of births using C57BL/6j (control) and gp91phox-knockout (gp91phox −/- ) mice. The number of births in gp91phox −/- mice was found to be lower than that in control mice. We observed sequential increases in gp91phox, ROS, nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 (NLRP3), caspase-1, and interleukin-18 (IL-18), followed by increased expression of mucin1 (MUC1), in control mice. However, none of these markers were upregulated in gp91phox −/- mice. In addition, in control mice administered IL-18 or MUC1 inhibitors, the number of births decreased to a number similar to that of gp91phox −/- mice. These results suggest that ROS derived from gp91phox activity altered the inflammatory system and produced IL-18, which subsequently increased the expression of MUC1, thereby modulating fetal development. Abbreviations: IL-1 β: interleukin-1β; IL-18: interleukin-18; NLRP3: nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3; IgA: immunoglobulin A; MUC1: mucin1